Association between Distribution Timeliness and Plate Waste of High Energy High Protein Diet in Hospital - Khoiriani, Izzati Nur; Mawadda, Ferinda Rahma; Wicaksari, Sifa Aulia; Prasetyo, Teguh Jati; Rahmah, Hiya Alfi; Handayani, Sri (Ikatan Sarjana Gizi Indonesia (ISAGI), 2024)
Plate waste of patients is one of quality indicators of food service management in hospitals. High energy and protein diet often produced high plate waste which may related to some factors. This study aimed to assess the correlation between portion size accuracy and distribution time with plate waste among patients with high energy-protein diet in Hospital. The study design was cross-sectional study which participated 56 meal of patients in total. The data collection is conducted during August 2023. Variables of study consist of portion size accuracy, distribution time and plate waste. All of data were analyzed using Independent T-Test and Chi Square tests. The study showed that the average of food portions was not accurate and meal serving was accurate. Average plate waste ≥20% was found in staple foods, plant-based protein, vegetables, and extra food, while animal protein <20%. There was no correlation between portion size accuracy with plate waste. However, there was a correlation between timeliness of serving with plate waste of staple food, animal protein, and extra food. The study concluded there was no correlation between portion size accuracy of food with plate waste. However, there was a correlation between distribution time with plate waste of staple food, animal protein, and extra food.